PENILAIAN POTENSI OBJEK DAYA TARIK WISATA ALAM RIAM ENSILING DI DESA LUMUT KECAMATAN TOBA KABUPATEN SANGGAU - Mapa, Novi Hunberto; Hardiansyah, Gusti; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2018)
Assessement of natural tourist atraction is a systematic and balanced process or activity to collect information about everything that has the unique attrativeness and high values that attract tourist to visit certain places and regions. This research aims to determine the Potential Assessment of Tourist Attraction of Riam Ensiling in Lumut Village Subdistrict Sanggau Regency. The method used in this research is survey with interview technique and the tool used for data collection is questionnaire. The results of assessment of each criterion based on the standard of development classification of ADO-ODTWA A PHKA 2003 are assessment of tourist attraction, accessibility assessment, assessment social condition and the economy, assessment of supporting insfrastructure and assessment of the availability of clean water which scored 266,81. This showes that the Riam Ensiling is not potential to bedeveloped as a natural tourist attraction at present in the area of Lumut Village, Toba Subdistrict, Sanggau Regency. The Local Government (Regency Goverment) should be able to assist and facilicate the community optimaly in the development plan of the management of the natural attractions of Riam Ensiling and make necesarry efforts to improve access to the location as well as other facilities intensively regarding Riam Ensiling Both formaly and informally. Keywords: Attraction, Natural Tourism, Potential Assessment.